GEOCHEMICAL CHARACTERISTICS OF THE GEOTHERMAL FLUIDS IN THE AKROPOTAMOS AREA (MACEDONIA, NORTHERN GREECE) - Arvanitis, A.; Dotsika, E.; Kolios, N. (Bulletin of the Geological Society of Greece, 2016)
The geothermal field of Akropotamos produces fluids at temperatures up to 90oC. The waters from wells AKR-1, AKR-3, AKR-4, AKR-5 and AKR-6 at 30 86oC and TDS of 3.1-30.7 g/l are classified as Na-Cl type. The water from well AKR-2 at 46oC with TDS of 2.15 g/l belongs to Na-HCO3Cl type. The cold and sub-thermal waters (16.4- 27oC) in the area are considered as fresh or low salinity waters (TDS: 0.31-4.34 g/l) of various mixed types. The Na-Cl geothermal waters can be divided into two categories due to two different hot aquifers: (a) Τhe first shallow aquifer contains high salinity waters (TDS: 27.4 30.7 g/l) at 30-48oC located within sands, sandstones and gravels. (b) Τhe second deeper reservoir composed of calcareous conglomerates and sandstones contains lower salinity waters (TDS: 3.1-5.08 g/l) at 83-90οC. The contribution of seawater to the chemical composition of the thermal waters in the shallow aquifer system seems to be important. With the aid of chemical geothermomometers applied to the geothermal water from well AKR-1, the deep temperature has been estimated to be >120oC. Significant quantities of CO2 are encountered in wells AKR-1 and AKR-3.